Behavior of Pregnant Women Toward Environmental Exposure Tobacco Smoke - Juli Oktalia (GoAcademica Research & Publishing, 2023)
Because it is responsible for the deaths of approximately 6 million people each year, smoking is one of the most significant challenges confronting the world of health. More than 5 million individuals lost their lives as a direct result of smoking cigarettes, and another 600 thousand lost their lives as a result of being exposed to cigarette smoke. It is possible for pregnant women to give birth to stillborn babies, malnutrition, disrupt the metabolism of fetal growth, have weak fetuses, and have disorders of the fetal nervous system if they are exposed to cigarette smoke. Because of this, the purpose of this study is to determine how pregnant women react to the presence of cigarette smoke in their homes that is produced by other people. Quantitative research is the method of investigation that was utilized in this study. The study also took a cross-sectional approach and utilized an analytic research design. The findings demonstrated that the attitudes of pregnant women and the value systems of pregnant women towards other people's cigarette smoke in the home environment is the most dominant element for the establishment of active smokers' awareness not to smoke in the home environment.